Global Report on Corruption in Sport - United Nations Office on Drugs; Crime (United Nations, 2024)
Offering for the first time a truly comprehensive look at corruption in sport, the Global Report on Corruption in Sport reveals the staggering scale, manifestation, and complexity of corruption and criminal networks in sport at international and national levels. While corruption in sport is not a new phenomenon – fraudulent activities in the running of sports institutions and competitions have been documented from the times of the Ancient Olympic Games – the past two decades have witnessed a substantial increase in criminal activities within this area. Indeed, a range of factors left it ripe for manipulation, with the perfect storm of globalization, a huge influx of money, the rapid growth of legal and illegal sports betting, and technological advances transforming the way sport is played and consumed and are making it increasingly attractive presented significant opportunities for to criminal networks seeking to exploit sport for illicit and illegal profit to capitalize.